Indocyanine green fluorescence in second-look surgery for necrotizing enterocolitis: enhancing the surgeon's perception - Pfennigs, Antonia Maximina; Besendörfer, Manuel; Diez, Sonja; Reingruber, Bertram (Frontiers in Pediatrics, 2025)
BackgroundA perfusion mismatch in the premature gut is the key component in the development of necrotizing enterocolitis (NEC). Resulting necroses need to be surgically excised, while intestinal salvage is crucial to the survival and rehabilitation of affected preterm neonates. Until now, resection margins have been based on standard visual inspection and surgical experience due to the lack of objective criteria for bowel viability. We hypothesize that by evaluating the vitality and perfusion during NEC surgery, necrosis margins can reliably be defined by indocyanine green (ICG) fluorescent imaging, a real-time visualization method, which has already been implemented safely in pediatric surgery for other indications.Materials and methodsIn a prospective study at our Level 1 Perinatal Center, patients were recruited after primary emergency surgery confirming NEC. Due to the acute phase of the inflammatory process, the extent and dynamics cannot be clearly defined at this point. Informed consent of the parents for the second-look surgery included ICG fluorescent imaging (0.04–0.7 mg/kg body weight), which was applied after completely exposing the intestinal bundle to visualize blood perfusion intraoperatively. ICG perfusion of intestinal tissue was visualized by a near-infrared camera and was compared with bowel vitality as judged conventionally by an experienced surgeon. Based on the findings, further treatment was specified. We correlated our surgical findings with subsequent histopathology.ResultsSix patients treated at our perinatal center met the inclusion criteria. In four patients, ICG-negative, non-vital gut areas were detected and resected with narrow margins of <1 mm. Histology and the further medical course proved to be consistent with these intraoperative results. In two patients, the clinical appearance of complete necrosis of the small intestines was confirmed by ICG fluorescence, supporting the decision to provide palliative treatment. In two out of six patients, clinical judgment and real-time ICG fluorescence were contradictory. Here, histopathology confirmed complete necrosis of the bowel in full accordance with ICG.ConclusionOur prospective cohort study gave evidence for ICG fluorescence to be useful and reliable in objectifying blood perfusion and intestinal vitality during NEC surgery, adding objectiveness to the surgeon's personal experience.